The multiple facets of corporate purpose: an analytical typology - Besharov, M; Mitzinneck, B (INFORMS, 2023)
As firms increasingly adopt a corporate purpose, there is substantial variation in what this turn to purpose actually entails and divergent views about whether and how firms can realize their purpose aspirations. To capture this variation and analyze its implications for enacting purpose, we leverage three existing bodies of research in organization and management theory: Early organization theory illuminates uses of purpose to convey an organization’s overarching reason for being, organizational hybridity sheds light on purpose as an alternative organizational objective to profit maximization, and systems perspectives offer tools for explaining purpose as a catalyst of systemic change beyond the boundaries of the firm. The typology that we develop based on these three bodies of research provides analytical clarity about distinct facets of the corporate purpose phenomenon and surfaces complementary insights into challenges and opportunities associated with purpose enactment. In doing so, it illuminates the value of drawing on existing organization and management theories for advancing corporate purpose scholarship and provides a springboard for future research.